PEMANFAATAN LIMBAH KULIT JAGUNG UNTUK MENINGKATKAN PEREKONOMIAN DI DESA - Novi Darmayanti (LPPM Universitas Islam Darul 'Ulum Lamongan, 2021)
The purpose of community service is to provide a pilot and training for the community in the form ofcraft making which utilizes corn husk agricultural waste as an effort to utilize the environmental potential ofPejok Sub-District, Kepohbaru Sub-District, Bojonegoro Regency. The method used is giving material anddemonstration. Characteristics of Pejok village community, especially mothers, mostly as housewives, theexistence of this training is to increase knowledge about the benefits of corn husk waste as raw material formaking handicrafts that have a sale value. In 6 months the farmers do 2 harvests. If in one harvest the farmerscan produce as much as 3 tons of waste, then it can be calculated in half a year producing as much as 6 tons. If 1ton produces 2000 handicrafts that sell for 50 thousand / craft then the income is 100,000. Means that if 6 tonswill produce a selling value of 120,000. So the business of utilizing corn husk waste is quite feasible to bedeveloped and can improve the economy of farmers or residents in Pejok village around 80% percent.